Randomised clinical trial: a Lactobacillus GG and micronutrient‐containing mixture is effective in reducing nosocomial infections in children, vs. placebo. Issue 6 (28th July 2016) - Bruzzese, E.; Fedele, M. C.; Bruzzese, D.; Viscovo, S.; Giannattasio, A.; Mandato, C.; Siani, P.; Guarino, A.
Summary: Background: Nosocomial infections are a major public health issue and preventative strategies using probiotics and micronutrients are being evaluated. Aim: To investigate the efficacy of a mixture of Lactobacillus GG and micronutrients in preventing nosocomial infections in children. Methods: A randomised, double‐blind, placebo‐controlled trial was conducted in hospitalised children. Children (6 months to 5 years of age) received Lactobacillus GG (6 × 10 9 CFU/day) together with vitamins B and C and zinc or placebo, for 15 days, starting on the first day of hospitalisation. The incidence of gastrointestinal and respiratory nosocomial infections after discharge was determined by follow‐up telephone call at 7 days. After 3 months, another telephone call estimated the incidence of further infections during follow‐up. Results: Ninety children completed the follow‐up. Of 19/90 children with a nosocomial infection (20%), 4/45 children (9%) were in the treatment group and 15/45 (33%) in the placebo group ( P = 0.016). Specifically, 2/45 (4%) children in the treatment group vs. 11/45 (24%) children in the placebo group ( P = 0.007) presented with diarrhoea. The duration of hospitalisation was significantly shorter in the treatment group (3.9 days ± 1.7 vs. 4.9 ± 1.2; P = 0.003). At the follow‐up, a total of 11/45 (24.4%) children in the treatment group had at least one episode of infection compared to 22/45 (48.9%) in the placebo group ( P = 0.016). Conclusion: A mixture containing Lactobacillus GG and micronutrients may reduce the incidence of nosocomial infections, supporting the hypothesis that this may represent a valid strategy to prevent nosocomial infections.